Oppressed Communities Struggle to Be Free from The Seed of "Othering" - Imbran Batelemba Bonde (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2023)
This article aims to analyze the circle of “othering” in Poso and how to cope with it. To investigate this, by conducting library research and participatory observation, I look back at the history of evangelism, which was introduced by NZG, and the conflict events that occurred in 1998-2007. By only limiting the study to Christian communities living in two villages I found that these two events were the key moments of how the “seeds” to “othering” people grew in some Christian societies. In addition, the approach to peace which only focuses on direct violence, still leaves trauma and structural violence from generation to generation, which in turn also creates suspicion among religious communities. In the end, through my observations of several events and social interactions that occur “naturally” in society, I propose the idea of building sustainable peace that has been practiced by several community groups in the present, through encounters with others, and building peace through the table fellowship.